Dung Beetles (Coleoptera: Scarabaeidae) Composition to Three Different Ecosystem Functions: A Study Case in Malaysia - Abdullah Muhaimin Mohammad Din,; Wan Madihah Abd Halim,; Sharifah Zulaikha Syed Ahmad ,; Salmah Yaakop, (Tropical Life Sciences Research, 2019)
Dung beetles (Coleoptera: Scarabaeidae) are sensitive towards habitat composition, change, and loss. This study was carried out to investigate the diversity of dung beetles in three forest ecosystems and the habitat association. Six sampling sites represented secondary forest (Bangi Reserve Forest [BRF] and Sungkai Reserve Forest, Sungkai), recreational forest (Langkawi Island, Langkawi and Fraser’s Hill [FH]) and wetland forest (Bera Lake [BL] and Chini Lake [CL]) have been chosen. A total of 15 pitfall traps were set up in three line transects rotten fish as bait. The dung beetles were collected in 24 h, 48 and 72 h. A total of 3,920 individuals with 40 species were successfully collected in which Sungkai has the highest collection followed by CL, BRF, FH, and Langkawi respectively. Based on the dendrogram, both wetlands site clustered together due to high similarity of species composition. BRF and Langkawi are also clustered together which may due to “island effect” occurred to BRF. In term of species composition and distribution, species from Clade 1 and 2 considered as less specific towards environment due to its presence in most ecosystems, while Clade 3 and 4 are more specific to certain ecosystem. In conclusion, besides dung beetles are used to measure ecosystem healthiness, it also can be specific to certain ecosystem types. Kumbang najis (Coleoptera: Scarabeidae) sensitif terhadap komposisi, perubahan dan kehilangan habitat. Kajian ini dijalankan bagi mengkaji kepelbagaian kumbang najis di tiga ekosistem hutan yang berbeza. Enam lokasi persampelan mewakili hutan sekunder (Hutan Simpan Bangi [BRF] dan Hutan Simpan Sungkai, Sungkai), hutan rekreasi (Pulau Langkawi, Langkawi dan Bukit Fraser [FH]) dan hutan tanah bencah (Tasik Bera [BL] dan Tasik Chini [CL]) telah dipilih. Sejumlah 15 perangkap lubang yang disusun di dalam tiga transek dengan menggunakan ikan busuk sebagai umpan telah dipasang. Sampel kumbang najis diambil dalam setiap 24, 48 dan 72 jam. Sejumlah 3,920 individu dengan 40 spesies telah berjaya dikumpulkan dengan Sungkai merekodkan jumlah tertinggi dan diikuti oleh CL, BRF, FH dan Langkawi. Berdasarkan dendrogram, kedua-dua kawasan tanah bencah dikumpulkan di dalam klad yang sama disebabkan kesamaan yang tinggi dalam komposisi spesies. BRF dan Langkawi juga berada dalam kumpulan yang sama yang mungkin disebabkan berlakunya “kesan pulau” terhadap BRF. Bagi komposisi spesies pula, Klad 1 dan 2 merupakan spesies yang umum yang kurang spesifik terhadap kebanyakkan ekosistem, manakala Klad 3 dan 4 lebih spesifik terhadap ekosistem tertentu. Kesimpulannya, selain kumbang najis digunakan bagi menentukan tahap kesihatan ekosistem, ia juga boleh menjadi spesifik kepada jenis ekosistem.